Incorporating cultural competency skills in emergency management education. Issue 5 (2nd November 2015) - Knox, Claire Connolly; Haupt, Brittany
Abstract : Purpose: – The purpose of this paper is to incorporate a model of prejudice reduction and cultural identity development theory to assess: the implementation of a diversity case study in a disaster management course; and the cultural competency understanding among the students. Design/methodology/approach: – A diversity case study was implemented in an undergraduate Disaster Response and Recovery course (Fall 2013 n =17; Spring 2014 n =21; Fall 2014 n =35). The discussion encouraged students to contemplate how their biases, preconceived notions, and stereotypes affect their future role in emergency management. Findings: – Results from Likert scale pre/post tests showed a marked increase in knowledge and a positive change in attitudes ( p < 0.05). Open-responses denoted linkages to the prejudice reduction model and cultural identity development theory. Research limitations/implications: – Bias can be attributed to the instructor and facilitator, and contextual limitations including a lack of: previous conversations and courses on diversity-related topics and participation motivation. Practical implications: – By developing cultural competency, managers initiate intergroup contact reducing negative perceptions and increasing empathy for those deemed different. Integrating cultural competency into emergency management academic programs allows students to identify how their biases, stereotypes, and preconceived notions affect their performance. Originality/value: – This study contributes to the literature by focussing on implementing a diversity case study to explore cultural competency, which is lacking in emergency management higher education. The diversity case study and instructional design could be adopted in disaster management courses.